Evaluation of the effect and investment benefit of Marine ecosystem protection and restoration - Xu, Lifeng; Liu, Dandan (Frontiers in Ecology and Evolution, 2022)
In order to explore the effectiveness of Marine ecosystem conservation and restoration, an evaluation method based on the effectiveness and investment benefit of Marine ecosystem conservation and restoration was proposed. This method recommends key technical problems and solutions based on the information represented by Marine ecosystem protection to explore the effectiveness of Marine ecosystem protection and restoration. The results show that the evaluation efficiency of Marine ecosystem protection and restoration and investment benefit is about 30% higher than that of traditional methods. Due to the uncertainty of Marine ecological restoration, the role of adaptive management in Marine ecological restoration has been paid more and more attention, and the systematic process of improved management adapted to new knowledge and information has been explored.